RESPONSE TO THE MINISTRY OF RELIGIOUS AFFAIRS' QUR ‘ANIC TRANSLATIONS: A Case Study of The Emergence of UII Qur'anic Translations (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
Studies in Qur'an translation projects today focus on translation projects by government institutions and individuals, even though non-government institutions also contribute to Qur'an translation projects in Indonesia. This article discusses the production of the translation of the Qur'an by the Islamic University of Indonesia (UII), namely "Al-Qur'an Karim and its Meaning Translation" as a response to the translation of the Qur'an by the Ministry of Religious Affairs. This article focuses on the reasons for the translation of the Qur'an by UII and the relationship between its formation and the translation of MoRA. This article also seeks to examine the extent of changes in the shift between the translation of the Qur'an of MoRA and UII. This research is a literature study based on library data related to the object of this study. Technically, the limited availability of the Qur'an from the Ministry of Religious Affairs gives rise to the translation of the UII Qur 'an. On the other hand, the UII translation was born as a more scientific, scientific, and multipurpose translation in response to verses that seemed to be masculine and discriminatory bias in the translation of MoRA which was translated harfiyah. The shift in differences between the Ministry of Religion Translation and UII Translation lies in the use of tafsiriyah UII translation methods and their reference sources which involve the use of literature on the essence of scientific polemics, resulting in differences in the results of translation. Meanwhile, in terms of publication format, layout,  text writing standards, and translation structure, it can be said that UII translations follow the standards of MoRA in contemporary editions.